Application of Teachings in the Sabbāsavasutta for Managing Stress - Metteyya, Ven. Beliatte (Journal of International Buddhist Studies, 2019)
The purpose of this article is to study the ways to apply teachings in the Sabbāsavasutta to manage stress. First of all an introduction to the severity of the stress and significance of finding new ways to overcome stress is given. Then the way to apply the method of seeing has been analytically presented. The importance of obtaining a clear view is emphasized in this step. Afterwards the ways to apply the methods of restraining, using, endurance, avoidance, removal have been presented accordingly. Finally the ways to apply the method of development has been elaborated emphasizing the fact that the development of positive factors is essential as well as the control and elimination of the negative aspects.